Working life expectancy of physicians: the case of primary care physicians in Czechia - Havelková, Tereza; Šídlo, Luděk (Human resources for health, 2025)
BACKGROUND: The decrease in the number of healthcare workers and the resulting deterioration in healthcare quality and availability have been subjected to intensive discussion in Czechia in recent years. Estimating future healthcare worker capacities requires a detailed analysis of their "movement" within the healthcare system. This study focuses on exits of the primary care physicians from the healthcare system in Czechia. METHODS: Using anonymised data obtained from the largest Czech health insurance company (2012-2022), we constructed working life tables and calculated working life expectancy, which indicates the expected average number of remaining years of work at the exact age of the physician. The study focuses on primary care physicians, who are crucial for the effective functioning of the healthcare system. RESULTS: At age 50, working life expectancy was 20 years for female physicians and approximately 21 years for male physicians. Over the monitored period, working life expectancy decreased by 1 year for both genders. Gynaecologists had the longest working life expectancy, while dentists had the shortest. CONCLUSIONS: The decrease in the working life expectancy and the length of tenure indicates the need to create favourable conditions for the extension of the working lives of physicians to avoid early exits from the system.
Keywords: dospělí; Female; Working life expectancy; naděje dožití; Adult; ženské pohlaví; lékaři; lidé; Physicians; Primary care physicians; Middle Aged; Physicians, Primary Care; Male; Czech Republic; Czechia; Česká republika; lidé středního věku; mužské pohlaví; lékaři primární péče; Healthcare system; Life Expectancy; Life tables; Humans